A deliberately forgotten battle: The Lapiang Manggagawa and the Manila Port Strike of 1963. (June 2022) - Scalice, Joseph
Abstract : This article documents a significant and previously unknown episode in the history of Philippine labor, the explosive Manila Port Strike of the arrastre service workers—stevedores and longshoremen—in 1963. The strike was among the largest, costliest and most politically charged labor struggles in the nation's history and yet not only has no account of it been written, it has found no mention in over a half-century of historiography. Using confidential US State Department memoranda, contemporary newspaper accounts, Partido Komunista ng Pilipinas (PKP) publications, and material published by the Lapiang Manggagawa (LM), I reconstruct the history of the strike. This article examines how an event of this magnitude, while still part of living memory, could disappear from the historical record. The case of the 1963 Port Strike highlights the need to recover the histories of the oppressed by reading not only the official archives, but also the narratives of the workers' own organisations, against the grain.